Analisis Taqlid dalam Perspektif Ushul Fikih Modern: Kontekstualisasi Ijtihad dan Reorientasi Otoritas Keilmuan - Aji, Ahmad Mukri (BULETIN ADALAH, 2025)
This study examines taqlid within the framework of modern ushul al-fiqh, focusing on its relationship with the contextualization of ijtihad and the reorientation of scholarly authority. It argues that classical taqlid functioned as a necessary epistemological mechanism to preserve legal stability, rather than as an obstacle to intellectual progress. Through a comparative analysis, the study shows that contemporary critiques often conflate legitimate taqlid with uncritical imitation. Modern ushul al-fiqh reconstructs taqlid as methodological adherence that supports collective and context-sensitive ijtihad. The study concludes that redefined taqlid complements ijtihad, ensuring continuity, legitimacy, and adaptability of Islamic law in rapidly changing social and intellectual contexts. Keywords: Taqlid, Ijtihad, Ushul al-Fiqh